Design Of SPP Payment Information System Using Midtrans Payment Gateway At SMK Pujangga Pasar Kemis - Harfizar Harfizar; Taufikurrahman Saleh; Ferda Delita Wati Waruwu (Jurnal Ilmiah Sains dan Teknologi, 2025)
Pujangga Pasar Kemis Vocational School is currently facing challenges in the tuition payment process which is still done manually, causing service delays, data security risks, as well as the possibility of data loss and errors in making reports. Difficulty in tracking payment data if the SPP payment card is lost is also a problem. To increase administrative efficiency, maintain data security, transparency, and provide better services, it is necessary to develop a technology-based tuition payment information system. The author collects information through observations and interviews with stakeholders to design an effective and structured tuition payment system. The PIECES system analysis method and system design using UML (Unified Modeling Language) are used to describe the design of this system. This system will be developed using the PHP programming language and MySQL database, with the help of XAMPP tools for data storage and management.